A viable supranational court born from the experiences of the demise of the Southern African Development Community Tribunal - Mchunu, Siphesihle (Department of Commercial Law, 2016)
Does the effective disbandment of the SADC Tribunal and its mooted resurrection in a largely diminished capacity spell the end of any possibility of developing a supranational organ capable of adjudicating on disputes between SADC members, as well as disputes between natural persons and Member states as was originally envisioned in Article 15 of the Protocol on Tribunal & Rules Thereof ("the Protocol")? Background The basis of the research question stems from the effective disbandment of the SADC Tribunal arguably as a result of the Republic of Zimbabwe's controversial land redistribution program and the recent developments surrounding the SADC Tribunal following the redrafting of the Protocol ("the New Protocol") by the Ministers of Justice of each Member State. The disbandment in essence being as a result of the land reform program adopted by the Zimbabwean Government in 2000 which raised various issues both politically and socially, however it was the legal issues brought on by the litigation which ensued that caused the most debate. In Mike Campbell (Pvt) Ltd. and Others v. Republic of Zimbabwe (2008) SADCT 2/2007 ("the Campbell Case") the SADC Tribunal held that the Zimbabwean Government should pay the applicants fair compensation for their expropriated land, take all necessary measures to protect the possession, occupation, and ownership of the land and ensure that no action was taken to evict the farmers or interfere with their peaceful residence of their properties. Subsequent to the SADC Tribunal's finding as mentioned above, the applicants sought to have the SADC Tribunals rulings registered as an order of court in Zimbabwe in Gramara (Pvt) Ltd v. Government of the Republic of Zimbabwe (HC 33/09) [2010] ZWHHC [Harare High Court] which was dismissed by Zimbabwe's High Court. There is no doubt that the SADC Tribunals ruling in the Campbell Case and the prospective ramifications a ruling of that nature could have on each SADC states government policy reverberated through the office walls of each head of state. The Ruling showcasing perhaps a lack of appreciation with regards to what far reaching implications of subordinating a measure of sovereignty to a supranational body could have on government policy. In any case, subsequent to the Tribunals ruling in the Campbell Case followed an onslaught by the government of Zimbabwe regarding the Tribunals jurisdiction and its impartiality, all in an attempt to deligitimatise the institution. This onslaught succeeded in having the Tribunal disbanded, however in the wake of this a new Tribunal has been mooted to take its place. A New Protocol is currently being debated amongst regional leaders. The developments surrounding the SADC Tribunal following the signature of the New Protocol by 9 heads of state, is of concern considering the fact that Articles 14 and 35 of the New Protocol substantially moderate the jurisdiction and applicable law of the SADC Tribunal. The legal text in its current format is likely to vastly diminish the effectiveness of the SADC Tribunal reducing it to nothing more than a paper tiger. The research this paper intends on focusing on shall be with regards to what lessons can be learnt from the disbandment of the SADC tribunal by the SADC member states, with a view to establishing a supranational organism capable of adjudicating conflicts between member states whilst being cognizant of member states undertakings to observe human rights. Whilst also looking at the weaknesses of the old Tribunal, insofar as transposing a Eurocentric model into Africa , which has conditions not ideal for such a model.